Clinical Profile and Outcome of Patients Presenting with Mushroom Poisoning in a Tertiary Care Center of Eastern Nepal - Chaudhary, Shatdal; Chaurasia, Ramesh Kumar; Patel, Sushila; Agrawal, Krishna Kumar; Aswani, Rakesh; Jaiswal, Niraj Kumar (Journal of Nepal Medical Association, 2013)
Introduction: Accidental mushroom poisoning is constantly seen and regularly reported from all over world. Exact magnitude of problem and its clinical profile in Nepal is not well known. This study was done to evaluate clinical profile and treatment outcome of patients presenting with mushroom poisoning in the department of internal medicine, BPKIHS, Dharan. Methods: It is a prospective observational study conducted in department of internal medicine, BPKIHS, Dharan from 1st January 2008 to 31st December 2009. Informed consent was taken. All the patients were subjected to necessary laboratory investigation. They were followed up at 1 week and 1 month after discharge. Results: All together 60 patients were analyzed. Majority of subjects 56 (93.3%) were from rural areas. Vomiting and diarrhea were the two most common presentations seen in 56 (93.3%) subjects. The latent period for the symptoms were > 6 hours in 4 (6.7%) and < 6 hours in 56 (93.3%) subjects. Fulminant hepatic failure was seen in 6 (10%) subjects and among them 4 (66.7%) expired. After admission 3 (5%) subjects developed GI bleeding. Average duration of hospital stay was 4.6 days. In follow up recovery was complete in all subjects who survived the acute phase of poisoning. Conclusions: Especially in patients coming during rainy season mushroom poisoning should be considered in the differential diagnosis of acute gastroenteritis. Mortality is high in subjects with FHF whereas recovery is complete in subjects who survived the acute phase. Keywords: fulminant hepatic failure; gastroenteritis; mushroom poisoning; wild mushrooms.